The Efficacy and Safety of Celecoxib for Pain Management After Total Knee Arthroplasty: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Geng, Xiaoyuan; Zhou, Shangyou; Zhang, Xiaoyan; Liu, Xi; Cheng, Xu; Jiang, Lihua; Zhang, Donghang (Frontiers in Surgery, 2022)
Background This study aimed to determine the efficacy and safety of celecoxib for pain management after total knee arthroplasty (TKA). Methods PubMed, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL) were searched to identify eligible randomized controlled trials (RCTs) that compared celecoxib with a placebo in term of pain control efficacy after TKA. Primary outcomes included pain scores at 24, 48, and 72 h after TKA. Secondary outcomes included the active range of motion (ROM) at 24, 48,72 h, and 7 days postoperatively, morphine consumption over 72 h after TKA, incidence of postoperative nausea and vomiting (PONV), and total blood loss after surgery. Data analysis was conducted using RevMan version 5.3. Results Five RCTs involving 593 participants were included in the study. Compared with a placebo, celecoxib significantly reduced visual analog scale (VAS) scores at rest at 24 h [mean difference (MD) = −0.72; 95% confidence interval (CI), −1.27 to −0.17; I2 = 82%; P = 0.01], 48 h (MD = −1.51; 95% CI, −2.07 to −0.95; I2 = 0%; P < 0.00001), and 72 h (MD = −1.30; 95% CI, −2.07 to −0.54; I2 = 82%; P = 0.0009) after TKA, decreased morphine consumption over postoperative 72 h (MD = −0.73; 95% CI, −0.96 to −0.51; I2 = 96%; P < 0.00001), and increased active ROM at 48 h (MD = 13.23; 95% CI, 7.79 to 18.67; I2 = 0%; P < 0.00001), 72 h (MD = 6.52; 95% CI, 4.95 to 8.10; I2 = 68%; P < 0.00001), and 7 days (MD = 7.98; 95% CI, 3.64 to 12.31; I2 = 68%; P = 0.0003) after the operation. No significant difference was found in the active ROM at 24 h (MD = 7.60; 95% CI, −6.14 to 21.34; I2 = 94%; P = 0.28) and the incidence of PONV after surgery [risk ratio (RR) = 0.66; 95% CI, 0.40 to 1.09; I2 = 0%; P = 0.11]. Conclusion The administration of celecoxib is an effective and safe strategy for postoperative analgesia after TKA.